The human intestinal microbiome at extreme ages of life. Dietary intervention as a way to counteract alterations - Salazar, Nuria; Arboleya, Silvia; Valdés, Lorena; Stanton, Catherine; Ross, Paul; Ruiz, Lorena; Gueimonde, Miguel; de los Reyes-Gavilán, Clara G. (Frontiers in Genetics, 2014)
The intestinal microbiome is defined as the assembly of genomes from microorganisms inhabiting the gut. This microbial ecosystem regulates important functions of the host and its correct composition and functionality is essential for a “healthy status”. Metagenomic studies have highlighted variations of the intestinal microbiota as a function of age and diet. Colonization of the infant gut starts at birth and is influenced by feeding habits (formula vs. breast-feeding), birth mode and antibiotic exposure. The intestinal microbiota of full-term vaginally-delivered breast-fed infants is considered the gold-standard of a healthy infant microbiota, representing the reference for studies of alterations in other pediatric populations. At two to three years of age, the intestinal microbiota reaches a composition similar to adults, remaining without noticeable variations until senescence, when microbial instability and changes reappear. Here we summarize the current knowledge on intestinal microbiota alterations at extreme stages of life and tools for designing differentiated nutritional strategies by the use of probiotics, prebiotics and specific nutrients in order to restore a balanced microbiota and to improve immune and nutritional status.